Van a börtön, babám . Then There's Prison, Honey - Gábor, Ferenczi; Ágnes, Sós (Fehéri, Tamás ; Gergő, Ferenc ; Kavisánszky, Gusztáv ; Nagy, Gusztáv, 2000)
Duration: 01:20:00 For their documentary, the filmmakers accompanied three ex-convicts from the day of their release over a period of one year. What would await the men "outside"? What are their efforts to be re-integrated into society? What about the temptation to make a fast buck with new swindlings? 28 year old Gustzi, convicted for forgery of documents and fraud, can stay with one of his girlfriends for a start. He finds work at a circus but hardly makes enough money there to pay the alimony for his little son. Gustzav, 26 years old, gets a new tracksuit as a welcome home-present from his family. Determined to lead a decent life he starts looking for a job. He is skilled in handicraft and finds work on a building site. But it doesn't take long until problems arise. Ferenc has the most difficulties of them all. 24 of his 46 years he spent behind bars. After his release he lives with his cousin and works odd jobs. He spends half of his daily pay on alcohol in a bar, where he's telling tales of his robberies. Ferenc insists on being no professional thief, though - otherwise he wouldn't have been caught so often…